Sulfonylurea and neuroprotection: The bright side of the moon - Nawar R Hussien; Marwa S Al-Naimi; Huda A Rasheed; Hayder M Al-kuraishy; Ali I Al-Gareeb (Wolters Kluwer Medknow Publications, 2018)
Sulfonylurea (SUR) agents are the second and most used oral hypoglycemic drugs after metformin and they still as an imperative tool for most favorable of glucose control. SURs are used mainly in the management of Type 2 diabetes mellitus since; they are effective in the glycemic control and reduction of microvascular complications. First-generation SUR represents 3% of used oral hypoglycemic agents while second and third generations are used in about 25% in patients with Type 2 diabetes mellitus. Upregulation of SUR1 receptor has been observed after stroke and traumatic brain injury, therefore, SUR such as glibenclamide inhibits brain edema and astrocyte swelling following brain insults. SUR drugs mainly glibenclamide is effective at a low dose in the management of cerebral stroke and could be a contestant with corticosteroid in controlling brain edema.